2008
DOI: 10.1007/s11250-008-9129-2
|View full text |Cite
|
Sign up to set email alerts
|

The detection of antibody against peste des petits ruminants virus in Sheep, Goats, Cattle and Buffaloes

Abstract: Monoclonal antibody-based competitive ELISA (C-ELISA) has been used for the specific measurement of antibodies to peste des petits ruminants (PPR) viruses in sheep, goats, cattle and buffalo. Serum samples from sheep (n = 232), goats (n = 428), cattle (n = 43), buffalo (n = 89) were tested. The animals had not been vaccinated against rinderpest or PPR. Findings suggested that the sero-positive cases were significantly higher in sheep (51.29%) than in goats (39.02%) (P = 0.002). The overall sero-prevalence of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 18 publications
8
49
1
Order By: Relevance
“…A difference in the neutralising PPR antibodies in the sheep may be sensitivity to PPR virus, which was correlated to breed because sheep only suffer mild to inapparent infection rather than to the virus, was reported among various with the virus or this may be attributed to a higher breeds of goats [22,23]. PPR is the singular most recovery rate and a greater longevity of sheep verses important cause of morbidity and mortality among goats which is similar to the serological profile small ruminants, for which the most effective form of reported earlier by some workers [30,31,32]. Some protection is through vaccination or an eventful workers have reported a PPR outbreak in a flock of recovery from natural infection.…”
Section: Resultssupporting
confidence: 60%
“…A difference in the neutralising PPR antibodies in the sheep may be sensitivity to PPR virus, which was correlated to breed because sheep only suffer mild to inapparent infection rather than to the virus, was reported among various with the virus or this may be attributed to a higher breeds of goats [22,23]. PPR is the singular most recovery rate and a greater longevity of sheep verses important cause of morbidity and mortality among goats which is similar to the serological profile small ruminants, for which the most effective form of reported earlier by some workers [30,31,32]. Some protection is through vaccination or an eventful workers have reported a PPR outbreak in a flock of recovery from natural infection.…”
Section: Resultssupporting
confidence: 60%
“…Specific antigen could be detected in the unvaccinated control animals after challenge but not from any of the immunized goats. The antibody titres against PPR in cattle and buffalo have also been reported by Khan et al (2008). Therefore, it is suggested that, within villages where PPR vaccination is administered in small ruminants, cattle in close contact with sheep/goats could be considered sentinel animals and could be sampled for evidence of seroconversion.…”
Section: Discussionmentioning
confidence: 90%
“…57,59,62,65,66,67,68,70,72,74,79,80,81,84,86,87,88,89,90,93,94,95,97,98,99,105,106,109,112,113,114,116,117,118,119,120,121,125,126,128,130,131,132,133,135,137,138,139,141,142,145,147,…”
Section: Study Eligibility Form: Performance Of Diagnostic Tests For mentioning
confidence: 99%